Comparative Analysis of Pain Management Strategies Following Laparoscopic Cholecystectomy - Kalim, Muhammad; Asjad, Muhammad; Ahmed, Jawad; Qureshi, Muhammad Azhar; Bhatti, Tanvir Ahmad; Khan, Rumman (Journal of Neonatal Surgery, 2025)
Background: Although laparoscopic cholecystectomy is considered the standard and most effective procedure for treating gallstone disease, patients often report experiencing moderate postoperative pain within the first 24 hours following surgery This can hinder early mobilization and elongate their hospital stay. Recovery outcome and analgesic preference greatly impacts patient satisfaction along with postoperative discomfort. This investigation centered on evaluating the efficacy of three postoperative analgesic regimens: intravenous NSAIDs alone, NSAID-opioid combinations, and TAP block coupled with NSAID administration in patients who had undergone laparoscopic cholecystectomy. Methods: A total of 81 patients scheduled for Laparoscopic Cholecystectomy during the observational period were prospectively entered into the study with random allocation into three groups (n=27). Participants in group A only received intravenous non-steroidal anti-inflammatory drugs (NSAIDs), while group B patients received NSAIDs and opioids. Furthermore, patients in group C received TAP blocks along with intravenous NSAIDs. Pain was assessed using the ‘Visual Analogue Scale (VAS)’ at 2, 6, 12, and 24 hours. Time to first request for analgesia, total consumption of analgesics, incidence of nausea and vomiting, length of hospitalization, and overall patient-reported satisfaction concerning pain management were considered as secondary outcome measures. Results: Compared to groups A and B, participants in Group C (TAP bloc) exhibited a significant reduction in VAS scores at every measured time point (p < 0.001). Participants also consumed less opioids, had longer durations before analgesic requests, and faster recovery milestones indicating early mobilization as well as shorter duration of hospitalization. Satisfaction was maximum with TAP block; this group also reported the least postoperative nausea and vomiting. Conclusion: The use of TAP block with IV NSAIDs markedly enhances postoperative pain control, recovery, and patient satisfaction following laparoscopic cholecystectomy. This approach could significantly augment the multimodal analgesic strategy in conventional surgical care.